Distribution and morphological features of astrocytes and Purkinje cells in the human cerebellum - Christa Hercher; Christa Hercher; Kristin Ellerbeck; Louise Toutée; Xinyu Ye; Refilwe Mpai; Refilwe Mpai; Claudia Belliveau; Maria Antonietta Davoli; W. Todd Farmer; Alanna J. Watt; Keith K. Murai; et al. (Frontiers in Neuroanatomy, 2025)
IntroductionThe cerebellar cortex is now recognized as a functionally heterogeneous brain region involved not only in traditional motor functioning but also in higher-level emotional and cognitive processing. Similarly, cerebellar astrocytes also display a high degree of morphological and functional diversity based on their location. Yet, the morphological features and distribution of cerebellar astrocytes have yet to be quantified in the human brain.MethodsTo address this, we performed a comprehensive postmortem examination of cerebellar astrocytes in the healthy human brain using microscopy-based techniques. Purkinje cells (PCs) were also quantified due to their close relationship with Bergmann glia (BG). Using canonical astrocyte markers glial fibrillary acidic protein (GFAP) and aldehyde dehydrogenase-1 family member L1 (ALDH1L1), we first mapped astrocytes within a complete cerebellar hemisphere.ResultsAstrocytes were observed to be differentially distributed across cerebellar layers with their processes displaying known morphological features unique to humans. Stereological quantifications in three functionally distinct lobules demonstrated that the vermis lobule VIIA, folium displayed the lowest densities of ALDH1L1+ astrocytes compared with lobule III and crus I. Assessing cerebellar layers showed that the PC layer had the highest ALDH1L1+ densities while GFAP+ densities and astrocytes colocalizing (ALDH1L1+ GFAP+) were highest in the granule cell layer yet displayed the smallest GFAP-defined territories. PC parameters revealed subtle differences across lobules, with vermis folium VIIA having the lowest PC densities while a trend for the highest BG:PC ratio was observed in the cognitive lobule crus I. Lastly, to determine if these features differ from those of cerebellar astrocytes and PCs in species used to model human illnesses, we performed comparative analyses in mice and macaques showing both divergence and commonalities across species.DiscussionThe present study highlights the heterogeneity of astrocytes in the human cerebellum and serves as a valuable resource on cerebellar astrocyte and PC properties in the healthy human brain.